ENT 530 Social Media Portfolio: Dadicted / Muhammad Daniel Abdul Razak - Abdul Razak, Muhammad Daniel (2021)
Dadicted offers a mouthful of classic Malay dessert, also known as ‘dadih,' that we elevate in taste and flavor for our beloved customers. Our company provides affordable products and services that can satisfy the craving consumer who wanted a special taste of ‘dadih' by providing a variety of flavors that are common among Malaysians. Furthermore, we provide a next-day delivery service on Mondays, Wednesdays, and Fridays to guarantee that the customer receives the freshest product possible so that they can enjoy their choice of dadih in bliss. Our target audience is a group of people with a sweet tooth, especially teens and children who enjoy trying new desserts that suit their tastes. Dadicted to also targeting any events such as weddings, birthday parties, and any banquet whether on a small or large scale to take advantage of the large crowds and promotions provided by us where any bulk orders can get special prices and discounts. Moreover, we have a particular region and coverage for our unique taste of dadih, such as in Selangor and Kuala Lumpur, with certain delivery charges. One of the reasons we made that decision was that we needed to deliver the dadih as quickly as possible, and the product, due to its taste, cannot last forever unless kept in a cold or refrigerated environment. We just choose the best options for our cherished customers to enjoy their dadih. Dadicted's marketing strategy is to offer a range of flavours of dadih at reasonable prices, which is special in the market. As a result, the distinct flavour of hand-crafted dadih is one of the factors that can be incorporated into our marketing effort to draw more consumers. Dadicted is now led by Muhammad Daniel, Hariz Azfar, and Ungku Izzat, who each play a specific role in the organization. Our company uses Facebook and Instagram as a medium to draw online customers, raise product visibility in the business community, and increase revenue all at the same moment. We will advertise Dadicted products and services on Facebook through teaser posts, soft sells, and hard sells as part of our strategy to spread the word about our business.